Feminisme dalam Pendidikan - Choirunniswah Choirunniswah (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2012)
In Islam, men and woman have equal right in obtaining education. But in reality, history of classic Islam shows that woman clan does not get the opportunity adequate in education of Islam which can send them to Moslem scholar. This matter can be comprehended in the eyes of public and perception pass by quickly, history source, specially dictionary of biography representing device of information hit this public impression, whether can be interpreted that there is no Moslem scholar woman, or at least is there any Moslem scholar of woman properly come into dictionary of certain biography? This article will study how in fact education of woman in Islam and what woman have role in science transmission?